Review paperUric acid and xanthine oxidase: perspectives in chronic heart failure - Patel, Pawan D.; Arora, Rohit R. (Archives of Medical Science, 2008)
Heart failure continues to be one of the major causes of morbidity and mortality in the western world. Advances in cardiovascular medicine have lead to unearth the possible markers of disease progression. Hyperuricemia is one of the potential metabolic markers for heart failure. In this review, we discuss the beneficial and deleterious role of uric acid and xanthine oxidase in the pathophysiology and management of chronic heart failure. Measurement of this readily available inexpensive marker may be included in the routine protocol and xanthine oxidase inhibition in addition to correct hyperuicemia may improve the vascular function and oxidative stress in patients with chronic heart failure.